Wakaf Tunai dalam Sistem Keuangan Islam: Konsep, Regulasi dan Implementasi - Effendi, Bahtiar (STAINI Press, 2024)
Waqf, in this case cash waqf, has only been understood as a sunnah worship that has a jariyah reward to be practiced. This kind of understanding makes waqf not develop even though waqf has socio-economic benefits to strengthen the financial system in Indonesia. The purpose of this research is to find out how the role of waqf in the Financial System, the discussion is focused on the concept, regulation and implementation of cash waqf in Indonesia. The method used is descriptive qualitative where the method is used to understand the symptoms that occur without requiring quantification. The results of the study explain that waqf has a very vital role in strengthening the Financial System in Indonesia. This role can be explained in the agricultural sector, as well as strengthening the national economy through the Cash Waqf Linked Sukuk (CWLS) program.